They Don't Want Her There : Fighting Sexual and Racial Harassment in the American University - Chalmers, Carolyn, 1946- (Book collections on Project MUSE., 2022)
"Before the nation learned about workplace sexual harassment from Anita Hill, and decades before the #MeToo movement, Chinese American professor Jean Y. Jew M.D. brought a lawsuit alleging a sexually hostile work environment in the College of Medicine at the University of Iowa. A young and ambitious researcher, Jew worked closely with her older male mentor upon arriving at the university. As she gained accolades and advanced through the ranks, she was met with increasingly vicious attacks on her character-implying that her sexuality had opened doors for her, and subjecting her to all manner of obscene gossip, even a lewd limerick scrawled on the men's bathroom wall. After years of a demoralizing combination of sexual, racial, and ethnic discrimination from the white men populating her department and determining the trajectory of her career, Jean Jew decided to fight back, and Carolyn Chalmers was her lawyer. This memoir tells the story of groundbreaking litigation unfolding over eight years through a University investigation, a watershed federal trial and a state court jury trial. In the face of a university determined to defeat them and maintain the status quo, Jew and Chalmers forged an exceptional relationship between a lawyer and a client, two professional women, each at the top of their game and part of the first generation of women in their fields. The result was extraordinary: a landmark civil rights battle at the"--